2022
DOI: 10.1128/mra.01206-21
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of Litorilinea aerophila, an Icelandic Intertidal Hot Springs Bacterium

Abstract: The hot springs bacterium Litorilinea aerophila PRI-4131 T (= ATCC BAA-2444 T ) was found in Isafjardardjup, in northwest Iceland. In this paper, we present a draft genome sequence for the type strain, with a total predicted genome length of 6,043,010 bp, 4,608 protein-coding sequences, 54 RNAs, 9 CRISPR arrays, and a G+C content of 64.61%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…7 ). Investigation on the 45 Chloroflexota genomes having FlaB (found in AnnoTree) and BlastP searches at NCBI (FlaB of strain JH545 as a query) revealed that at least two Chloroflexota strains harboring archaella gene cluster (flaB and several other genes) have been cultivated: Litorilinea aerophila 30 , 31 and Aggregatilinea lenta 32 (Supplementary Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…7 ). Investigation on the 45 Chloroflexota genomes having FlaB (found in AnnoTree) and BlastP searches at NCBI (FlaB of strain JH545 as a query) revealed that at least two Chloroflexota strains harboring archaella gene cluster (flaB and several other genes) have been cultivated: Litorilinea aerophila 30 , 31 and Aggregatilinea lenta 32 (Supplementary Fig. 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…This distribution suggests that archaella genes might have been transferred from Archaea to an ancestor of Chloroflexota and retained in the class Dehalococcoidia. Investigation on the 45 Chloroflexota genomes having FlaB (found in AnnoTree) and BlastP searches at NCBI (FlaB of strain JH545 as a query) revealed that at least two Chloroflexota strains harboring archaella gene cluster (flaB and several other genes) have been cultivated: Litorilinea aerophila 30,31 and Aggregatilinea lenta 32 (Extended Data Fig. 5).…”
Section: Genomic Featuresmentioning
confidence: 99%